Akibat Hukum Kelalaian Notaris Atas Akta Autentik terhadap Pihak yang Buta Huruf - Hidayatulloh Hidayatulloh; Nuzulia Kumala Sari; Galuh Puspaningrum (Referendum : Jurnal Hukum Perdata dan Pidana, 2026)
This study examines the legal consequences of a notary’s negligence in drafting an authentic deed involving illiterate parties. In notarial practice, a notary is required not only to comply with the formal requirements for preparing an authentic deed but also to ensure that the parties understand its contents and legal consequences. Legal issues arise when an illiterate party is involved, as the inability to read and comprehend the deed increases the risk of errors, abuse, and legal harm. This study employs normative legal research using statutory, conceptual, and case approaches. The findings reveal that notarial negligence may include failing to provide adequate explanations, failing to ensure the parties’ understanding, failing to verify their free consent, and focusing solely on administrative formalities. Such negligence may cause the deed to lose its authenticity, reduce its evidentiary value, result in its annulment, and undermine legal certainty. A notary’s liability may extend to administrative, civil, ethical, and criminal responsibility. Legal protection for illiterate parties may be provided through preventive measures, such as clearly reading and explaining the deed, as well as repressive measures, including civil litigation, complaints to the Notary Supervisory Council, and annulment of the deed. The study emphasizes the need to strengthen legal protection by reinforcing the prudential principle, the notary’s duty of care, and establishing specific standard procedures for handling vulnerable parties.